ISOLASI POPULASI DAN KARAKTERISASI BAKTERI Rhizobium PADA TANAH ASAL TAMAN NASIONAL GUNUNG HALIMUN - Purwaningsih, Sri (Research Center for Biology-Indonesian Institute of Sciences, 2002)
The studies on the isolation of population and characterization of Rhizobium bacteria have been carried out in soil samples from Gunung Halimun National Park. West Java. Soil samples taken from rhizospheres of rasamala (Altingia exsetsa), puspa (Schima wallichii)and kianak (Castanopsis aciaunaassima).Isolation was done in YEMA (Yeast Extract Mannitol Agar) medium, and the population done with MPN (Most Probable Number) method. The growth characteristic was observed by using YEMA medium mixed respectively with Brom Thymol Blue and Congo Red as indicators.The population of Rhizobium bacteria in YEMA medium was in the range of 0.28-35 5CFU/g